Graphene-hexagonal boron nitride resonant tunneling diodes as high-frequency oscillators - Gaskell, Jennifer; Eaves, Laurence; Novoselov, K.S.; Mishchenko, A.; Geim, A.K.; Fromhold, T.M.; Greenaway, M.T. (American Institute of Physics, 2015)
We assess the potential of two-terminal graphene-hexagonal boron nitride-graphene resonant tunneling diodes as high-frequency oscillators, using self-consistent quantum transport and electrostatic simulations to determine the time-dependent response of the diodes in a resonant circuit. We quantify how the frequency and power of the current oscillations depend on the diode and circuit parameters including the doping of the graphene electrodes, device geometry, alignment of the graphene lattices, and the circuit impedances. Our results indicate that current oscillations with frequencies of up to several hundred GHz should be achievable.